“The world doesn’t give things, you take things”: Deconstructing the Myth of the Self-Made Man in The Seven Husbands of Evelyn Hugo (2017) - Beatriz Carvalho (VIA PANORAMICA: Revista de Estudos Anglo-Americanos / A Journal of Anglo-American Studies, 2024)
ABSTRACT: Taylor Jenkins Reid’s novel The Seven Husbands of Evelyn Hugo, published in 2017, was an international success on social media, emerging in a time of political disarray in the Unites States of America with Donald Trump’s election. The book tells the story of a successful woman, Evelyn Hugo, who perfectly represents the self-made individual at the heart of the American Dream. Even if she has achieved worldwide fame and success by herself, this article will argue that this myth of the self-made man does not lead necessarily to a happy ending, following Evelyn’s own recounting of her story as one of profound grief and disenchantment. To deconstruct this myth, there will be an analysis of the different ways in which the character of Evelyn Hugo had to adapt to accomplish upward mobility, namely by agreeing to the objectification of her body, by erasing her ethnicity and sexual orientation, and by becoming someone immoral and self-serving, thus proving that this American myth does not pertain to everyone, nor does it imply and lead necessarily to happiness and personal fulfilment.